Profil Pustakawan Ahli Utama dan Pengukuhannya - Fathmi Fathmi; Arief Wicaksono (Media Pustakawan, 2020)
Pustakawan Ahli Utama is required to speech at the inauguration ceremony. Their number is 72 persons but not all of them had to speech. This study is to determine: the development arrangement and the process of the inauguration speech, their profile, include who has made the inauguration speech, and the reasons not made the script. The research was using a descriptive qualitative approach. The results found that Director National Library has not set the regulations yet. The inauguration speech process has administrative and scientific processes. The profiles of the Pustakawan Ahli Utama were 49 men and 23 women; educated as bachelor degree 33 persons, magister degree 37 persons, and  doctoral degree 2 persons; the rank of Pembina Utama is 9 persons, Pembina Utama Madya 53 persons, and Pembina Utama Muda 10 persons; worked at National Library 23 persons, university 18 persons, special libraries 14 persons and public libraries 13 persons; 34 persons are still active and 38 persons have retired. Main reason who has not made are they have not submitted DUPAK to IV / e, they have not socialized the regulations, they have difficulties for a script; they had not been told; and nearing retirement.